Financial literacy and its influence on internet banking behavior - Andreou, Panayiotis; Anyfantaki, Sofia (My University, 2020)
This paper presents the survey results for financial literacy among Cypriot adults and reports their financial aptitude and behaviour. Additionally, it investigates for the first time the implications of financial literacy on respondents’ usage of digital financial services, particularly internet banking (i-banking). The focus is on Cyprus, a country that experienced an unprecedented financial crisis in 2013 that resulted in a bail-in and an enormous subsequent shrinkage of the banking sector. Cypriot consumers face an ever-increasing need for financial sophistication to effectively utilise and manage digital banking services. Neverthless, financial literacy is still low in Cyprus, whereby only 37.33% of survey respondents showed proficiency in financial knowledge. The findings indicate that there is a statistically positive relationship between the levels of financial knowledge and the frequency of i-banking use. More importantly, financially illiterate consumers appear to report far more often than their financially literate peers the lack of trust in i-banking, as well as a lack of self-confidence in financial and digital skills as the main reasons for not using this service. The findings highlight the interplay between financial literacy and digital proficiency, and their implication on individuals’ use of i-banking services.
Keywords: Digital literacy; Financial innovation; Financial literacy; Internet banking; Personal finance